THE INFLUENCE OF COMPANY CHARACTERISTICS ON CSR DISCLOSURE IN MANUFACTURING COMPANIES LISTED ON THE IDX FOR THE PERIOD 2014-2016 - Manuel Aristo Surbakti (Universitas Maarif Hasyim Latif, 2023)
Corporate Social Responsibility Disclosure is a concept that brings companies to carry out their social responsibility towards external parties, namely the environment and society. Corporate Social Responsibility is decision-making related to ethical values, compliance with legal principles and decisions and respect for humans, society, and the environment. Corporate Social Responsibility is itended to encourage the business world to be more ethical in carrying out its activities so as not to have a negative impact on the community and the surrounding environment. This quantitative study aims to examine the effect of Company Characteristics on Corporate Social Responsibility Disclosure. The independent variables used in this study are 4 company characteristics, namely: board size, profitability, leverage, and company growth. The object of this research is a manufacturing company listed on the Indonesia Stock Exchange in the 2014 until 2016 period. The sampling technique used was purposive sampling. The sample in this study were 90 manufacturing companies listed on the Indonesia Stock Exchange in the 2014 until 2016 period. Data analysis technique using multiple linear regression. The results showed that profitability has an effect on Corporate Social Responsibility Disclosure. Meanwhile, the size of the board of commissioners, leverage, and company growth have no effect on Corporate Social Responsibility Disclosure